Accuracy of matrix-assisted LASER desorption ionization–time of flight mass spectrometry for identification of Candida. Issue 10 (11th October 2019) - Xie, Tian-Ao; Liu, Ye-Ling; Liang, Chuan; Huang, Yuan-Yuan; Li, Jin-Wei; Li, Zhong-Wei; Fan, Shu-Jin; Chen, Jin-Tao; Xia, Yong; Li, Xiao-Yan; Ouyang, Shi; Ji, Tian-Xing; et al.
Abstract: Background : Candida is a fungus that causes various types of candidemia, which is the fourth major infectious disease of the blood system. MALDI-TOF-MS is a simple and rapid detection instrument. The aim of the present study was to verify the accuracy of MALDI-TOF-MS in detecting Candida . Method : A pooled analysis of articles on MALDI-TOF-MS for diagnosis of candidemia was performed. The quality of original research was assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) guidelines. Stata 12.0 software was used to merge the correct identification rates of Candida and Candida subspecies and obtain pooled sensitivity and specificity of the diagnostic methods. Heterogeneity was found in the subgroup analysis of the included articles. Hence, we explored the factors causing the heterogeneity and its impact on the overall situation. Sensitivity analysis was used to examine the effect of Candida level on total response. Egger's test was used to evaluate the publication bias of the included articles. Results : A total of 16 articles in Pubmed, 79 articles in Embase, 1 article in Cochrane Library, 30 articles in Web of Science and 3 from other sources were identified, of which 10 articles were included based on the inclusion and exclusion criteria. The overall identification accuracy was 100%. Conclusion: The accuracy of MALDI-TOF-MS for the identification of Candida was 100%. Further research is necessary to determine whether MALDI-TOF-MS can be used as a clinical diagnostic standard for the identification of Candida .